Emergency intestinal stomas incidence and early complications - Sah, Bikash K.; A. Nashed, George; Ahmed, Ahmed N.; Raslan, Mohamed M. (International Surgery Journal, 2023)
Background: An intestinal stoma is a frequently performed procedure with a high percentage of complications. Even though creating an intestinal stoma is a procedure that can save lives while treating various gastrointestinal conditions, its accompanying morbidity and mortality have been the topic of many studies. This study was carried out in order to better understand a variety of complications in various types of intestinal stomas. Methods: A total of 60 patients with intestinal stoma construction in the general surgery emergency department at Kasr Al-Ainy emergency hospital Cairo, Egypt as an emergency procedure from December 2019 to May 2020 were included in this prospective cohort analysis. The inclusion criteria were all emergency cases undergoing intestinal stomas for treatment of either traumatic bowel injuries or acute abdominal surgical emergencies. Results: With a mean age of 45.18 years, 60 patients in all were evaluated. Males were 65% and females were 35%. End ileostomy with mucous fistula (33.3%) and loop transverse colostomy (18.30%) were the two stomas that were constructed most frequently. Intestinal obstruction (41.7%) was the most often reported indication of stoma formation. Complications of the peristomal skin made up the majority of cases (61.90%). Conclusions: This work significantly advances our understanding of stoma problems and their prevention to some extent through pre-operative soma site marking, good surgical technique, an experienced surgeon, a stoma therapy nurse, and patient education to enhance the care and quality of life for those who have stomas.